Policy Implementation of Law No. 35 of 2014 Regarding Child Protection in Cibeber District, Lebak Regency - Elly Nurlia*; Nurul Nursyiam; Said Ariyan (Riwayat: Educational Journal of History and Humanities, 2023)
Child protection is all the forms that are implemented that every child can get the rights and responsibilities to grow and develop naturally, both physically, mentally, and socially. The purpose of this research is to find out the implementation of Law No. 35 of 2014 on Child Protection Policy in Cibeber District, Lebak Regency. The research used descriptive qualitative methods and the basis for the use of research methods aims to collect and analyze a certain process related to the research focus. The data obtained are presented descriptively and analyzed using descriptive analytic techniques of the case study type. The theory used in this research is the Implementation Theory of Donald Van Metter and Carl Van Horn in Widodo (2008). The results of the study show that the Cibeber District Government has socialized child protection regulations quite well, this is evidenced by the role of the Cibeber District Government in collaboration with related parties such as the Health Party, Law Enforcement Officials, Village Government Parties, Social Assistance Parties (PATBM), to socialize and implement programs related to child protection, especially in Law No.35 of 2014. The obstacles found are the lack of public understanding of child protection regulations, as well as socio-economic conditions that result in gaps in the occurrence of violence against children, besides that the form of programs and socialization carried out by the government is not carried out in stages.